7.7k views
2 votes
K is the midpoint of JL JK=3x-1 and KL=2x+8 find JL

User Hfingler
by
4.1k points

2 Answers

3 votes

Answer: 52

Explanation:

I just solve the problem in khan academy

User Toby Van Kempen
by
5.1k points
0 votes

Answer:

JL = 52

Explanation:

It is given in the question that K is the midpoint of JL.

So, JK = KL ......... (1)

Now, given that, JK =3x - 1 and KL = 2x + 8

Therefore, from equation (1), we can write

3x - 1 = 2x + 8

x = 9

So, JK = 3x - 1 = 3(9) -1 = 26 and KL = 2x + 8 = 2(9) + 8 = 26

Hence, JL = JK + KL = 26 + 26 = 52. (Answer)

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.